2019
DOI: 10.2105/ajph.2019.305000
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Retail as a Strategy for Improving Food Security and the Built Environment in San Francisco

Abstract: In low-income neighborhoods without supermarkets, lack of healthy food access often is exacerbated by the saturation of small corner stores with tobacco and unhealthy foods and beverages. We describe a municipal healthy retail program in San Francisco, California, focusing on the role of a local coalition in program implementation and outcomes in the city’s low income Tenderloin neighborhood. By incentivizing selected corner stores to become healthy retailers, and through community engagement and cross-sector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 6 publications
0
31
0
Order By: Relevance
“…Sustainability has also been enhanced in some models with financial support from funds collected from imposed soda taxes, which may be a plausible future direction for the present model. 27 Corner stores remain a stable part of the local economy, often passed down from generation to generation and fall under the category of ''convenience stores,'' which accounted for 34% of the brick and mortar retail offerings in the United States, and 3.1% of gross domestic product in 2017 (yet, convenient stores which sell fuel account for 80% of stores in this grouping). 28 While it has been found that many people visit corner stores on a near daily basis, reduced access to such venues has been shown to reduce the obesity risk.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainability has also been enhanced in some models with financial support from funds collected from imposed soda taxes, which may be a plausible future direction for the present model. 27 Corner stores remain a stable part of the local economy, often passed down from generation to generation and fall under the category of ''convenience stores,'' which accounted for 34% of the brick and mortar retail offerings in the United States, and 3.1% of gross domestic product in 2017 (yet, convenient stores which sell fuel account for 80% of stores in this grouping). 28 While it has been found that many people visit corner stores on a near daily basis, reduced access to such venues has been shown to reduce the obesity risk.…”
Section: Discussionmentioning
confidence: 99%
“…To date, SSB tax revenues in the U.S. have been largely dedicated to health equity programs; accessibility of drinking water, physical activity, and healthy food, especially for children and low-income populations; public parks and recreation; healthy beverage campaigns; dental services; the CDC's Diabetes Prevention Program; nutrition education in public schools; universal prekindergarten; and community college tuition. [ [18] , [19] , [20] , [21] , [35] , [42] , [43] ] These programs aim to directly improve health or to address the social determinants of health (e.g., education), particularly in communities most affected by SSB marketing, consumption, and diet-related disease.…”
Section: Ethical Implications Of Ssb Excise Taxesmentioning
confidence: 99%
“…[ 62 , [71] , [72] , [73] ] Additionally, in the U.S., SSB tax revenues have largely been spent on promoting health and social equity. [ 18 , 19 , 21 , 35 , 42 , 43 ] Thus, SSB taxes may have a net benefit for low-income households. [23] …”
Section: Ethical Implications Of Ssb Excise Taxesmentioning
confidence: 99%
See 2 more Smart Citations